Analisis Perencanaan Struktur Perkerasan Runway, Taxiway, Dan Apron Bandara Sultan Syarif Kasim II Menggunakan Metode FAA - Brian Charles S; Sri Djuniati; Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Airport pavements are constructed to support the loads by aircraft using an airport. Pavements must be smooth surface, adequate of thickness, stable and not having distress. The purpose of this research are analyze pavement thickness landing movement such as runway, taxiway, and apron. Planning pavement thickness consist of flexible pavement and rigid pavement. Runway and taxiway using flexible pavement while taxiway using rigid pavement. Design pavementthickness landing movement refers to the method FAA (Federal Aviation Administration) Advisor Circular No : 150/5320-6D. Data movement of aircraft using air transportation data in2013 for scheduled flights. The analysis result shows the total pavement thickness runway, taxiway, and apron in a row is 75 cm, 68 cm, and 104 cm with aircraft plan B 737-900ER. While total pavement thickness for existing is 70 cm, 68 cm, and 117 cm.Keywords: Airport Pavement Design, FAA method, flexible and rigid pavement